Mystery Case: Dural melanocytoma with leptomeningeal melanocytosis. (28th February 2017) - Schembri, Mark; Kok, Hong Kuan; Brennan, Paul; O'Hare, Alan; Thornton, John; Looby, Seamus; Asadi, Hamed
Abstract : A 53-year-old man presented with a 1-month history of upper back pain. CSF examination was normal and imaging showed a midcervical avidly enhancing mass, with diffuse leptomeningeal abnormality (figure 1), suspicious for dural melanocytosis.